Potential Impact of Higher Food Prices on Poverty : Summary Estimates for a Dozen West and Central African Countries - Wodon, Quentin (World Bank, Washington, DC, 2012)
Concerns have been raised about the impact of rising food prices worldwide on the poor. To assess the impact of rising food prices in any particular country it is necessary to look at both the impact on food producers who are poor or near-poor and could benefit from an increase in prices and food consumers who are poor or near-poor and would loose out when the price increases. In most West and Central African countries, the sign (positive or negative) of the impact is not ambiguous because a substantial share of food consumption is imported, so that the negative impact for consumers is larger than the positive impact for net sellers of locally produced foods. Yet even if the sign of the impact is clear, its magnitude is not. Using a set of recent and comprehensive household surveys, this paper summarizes findings from an assessment of the potential impact of higher food prices on the poor in a dozen countries. Rising food prices for rice, wheat, maize, and other cereals as well as for milk, sugar and vegetable oils could lead to a substantial increase in poverty in many of the countries. At the same time, the data suggest that the magnitude of the increase in poverty between different countries is likely to be different. Finally, the data suggest that a large share of the increase in poverty will consist of deeper levels of poverty among households who are already poor, even if there will also be a larger number of poor households in the various countries.